2012
DOI: 10.5402/2012/596486
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine Augments Delta, Theta, and Right Frontal EEG Alpha Power in Schizophrenic Patients

Abstract: Objective. To explore the Quantitative EEG (QEEG) effects of established clozapine therapy regimes compared to those of previous ineffective antipsychotic regimes among 64 chronic (DSM-IV) schizophrenic patients. Methods. Data from 20 EEG channels referenced to linked ears were collected before and during maintenance clozapine therapy (mean duration 1.4 years). Absolute power was calculated in six frequency bands: delta (0.4–3.6 Hz), theta (4.2–7.8 Hz), alpha (8.2–11.8 Hz), beta1 (12.2–15.8 Hz), beta2 (16.2–19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
0
12
1
Order By: Relevance
“…These findings suggest that clozapine possibly affects attentive but not pre-attentive processing. Five studies used spectral analysis to assess effects of clozapine 6569. Two early studies65,66 measured coherence and showed that resistant patients display interhemispheric and intrahemispheric dysconnectivity over anterior brain regions that clozapine partially normalised.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that clozapine possibly affects attentive but not pre-attentive processing. Five studies used spectral analysis to assess effects of clozapine 6569. Two early studies65,66 measured coherence and showed that resistant patients display interhemispheric and intrahemispheric dysconnectivity over anterior brain regions that clozapine partially normalised.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies demonstrated the widespread effects of clozapine on spectral power, indicating both increases in fast wave and slow wave power. 6769…”
Section: Resultsmentioning
confidence: 99%
“…In addition, atypical antipsychotics (e.g. clozapine, quetiapine) are also used to treat psychosis in PD ( Wilby et al, 2017 ), and have been shown to increase power in lower frequencies and decrease power in higher frequencies ( Hyun et al, 2011 ; Maccrimmon et al, 2012 ). In our study, only two patients with multimodal hallucinations used atypical antipsychotics ( N = 1 clozapine, and N = 1 quetiapine).…”
Section: Discussionmentioning
confidence: 99%
“…The results of EEG frequency analyses demonstrated a decrease of central activation (power) in SZO in comparison to CON. It was proven [ 90 ], in general, that atypical antipsychotics like clozapine increase the central activation (power) in the δ and θ bands, especially in frontal brain regions, and thus, also directly affect, P EEG , The effects of placebo and antipsychotics (haloperidol, chlorpromazine, clozapine) were investigated by Small et al [ 91 ], who demonstrated that clozapine and chlorpromazine are associated with increased frontal δ central activity. In addition, the effect of antipsychotic treatment (clozapine) on clinical scores was demonstrated by significantly reduced positive and negative symptoms and global psychopathology [ 92 ].…”
Section: Discussionmentioning
confidence: 99%